1991
DOI: 10.1029/90ja02101
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ULF fluctuations in the solar wind, magnetosheath, and dayside magnetosphere: 1. Magnetosheath morphology

Abstract: “Upstream waves,” generated in the solar wind upstream of a quasi‐parallel bow shook, are believed to be a major source of the Pc 3‐4 pulsation activity observed in the dayside magnetosphere. In an attempt to better understand the means by which “upstream wave” energy is transmitted from the solar wind into the magnetosphere, we compared simultaneous data from ISEE 1 and 2 in the upstream solar wind, AMPTE IRM in the subsolar magnetosheath, and AMPTE CCE in the dayside magnetosphere. Our observations indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…the power of these waves in the magnetosphere should also depend on the solar wind speed.738 B. Heilig et al: Upstream waves observed in the topside ionosphere by CHAMP through the magnetosheath (Russell et al, 1983), enter the magnetosphere near the subsolar point of the magnetopause (Engebretson et al, 1991b;Krauss-Varban, 1994), propagate across the magnetosphere, enter the ionosphere and reach the ground as geomagnetic pulsations (Yumoto et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…the power of these waves in the magnetosphere should also depend on the solar wind speed.738 B. Heilig et al: Upstream waves observed in the topside ionosphere by CHAMP through the magnetosheath (Russell et al, 1983), enter the magnetosphere near the subsolar point of the magnetopause (Engebretson et al, 1991b;Krauss-Varban, 1994), propagate across the magnetosphere, enter the ionosphere and reach the ground as geomagnetic pulsations (Yumoto et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Engebretson et al [1994] later showed quantitatively that observed modulations of precipitating energetic electrons near the cusp were sufficient to generate the Pc3-4 pulsations simultaneously observed nearby on the ground. The mechanism(s) responsible for precipitating these energetic electrons are themselves poorly understood, although observational studies by Engebretson et al [1991b] and Linet al [1991a, b] suggested that large, highly localized variations in the dynamic pressure in the magnetosheath, generated by these upstream waves, may compress and distort regions near the dayside magnetopause and thus cause such precipitation. Their observations also indicated large bipolar excursions of the Bz component of the magnetosheath magnetic field on similar timescales which, interestingly enough, appeared to have little dependence on the sign of the (relatively small) IMF Bz component.…”
Section: Introductionmentioning
confidence: 99%
“…Not only transient perturbations at the magnetopause [Fairfield et al, 1990;Sibeck et al, 2003] and ULF pulsations in the magnetosphere Engebretson et al, 1991] are linked to the waves in the foreshock, but bow shock accelerated particles at times also appear in the magnetosphere [Fuselier et al, 2002]. An important region of such plasma penetrations is the magnetospheric cusp in which magnetic field lines are open to the magnetosheath allowing direct entry of the solar wind particles [Haerendel et al, 1978].…”
Section: Introductionmentioning
confidence: 99%